Optimizing the Role of Parents in Children's Educational Awareness in Kedungsugo Prambon Village, Sidoarjo - Sirojuddin, Akhmad; Syarifah, Syarifah; Rofiq, Irsyaddur; Karmuji, Karmuji; Mistar, Junaidi (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
This community service programme was conducted in Kedungsugo Village, Prambon District, Sidoarjo Regency, East Java. The programme identified several crucial problems: 1) Low parental awareness of children's growth and potential; 2) About 47% of the community is on the poverty line; 3) High school dropout rate at productive age; 4) Children working not in accordance with their expertise; 5) High divorce rate due to early marriage; 6) High risk of juvenile delinquency such as crime, alcohol, and drugs. The Doktor Mengabdi (KDM) group of Unisma Malang implemented this workshop programme using the Participatory Action Research (PAR) method, supported by data from the social services and village government. The aim is to overcome these crucial problems through increasing parents' awareness as the main driver of mindset change, optimising the role of parents, and increasing awareness of the importance of education for children and families. This effort aims to gradually reduce and eliminate problems such as school dropouts, early marriage, and juvenile delinquency. The benefits of this community service are in accordance with the needs of Kedungsugo Village and Unisma's vision and mission for global economic peace and equality, as well as supporting the government's SDGs programme which focuses on quality and equitable education and socio-economic development. The success of this community service can be seen from the enthusiasm of the community in participating in the programme and the positive response during the discussion, which is an indication of improving the quality of human resources as the main capital for change in the village.